A adesão ao tratamento, reações adversas e polimorfismos genéticos de G6PD em pacientes com hanseníase atendidos em uma unidade de referência de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Leprosy is a chronic infectious disease caused by the agent Mycobacterium leprae, manifested mainly through dermatological signs and symptoms. The condition is prevalent in Brazil and constitutes a serious public health problem in many parts of the world. The disease is treated through multidrug therapy (MDT), a combination of dapsone, rifampicin and clofazimine. Even though it is considered effective, this treatment can result in several adverse reactions attributed to MDT drugs, which can be more severe in patients who have G6PD deficiency. In the state of Amazonas, leprosy has significant prevalence rates and, for this reason, the following study proposed to study the relationship between adherence to treatment, adverse reactions and the genetic polymorphism of G6PD. The approach of the patients and the collection of data and blood samples were carried out at the Tropical Dermatology Outpatient Clinic of the Tropical Dermatology and Venereology Foundation “Alfredo da Matta” (FUAM). In the present study, 50 leprosy patients treated with MDT were evaluated. According to the results, most patients were male (58%) and the most affected age group was the economically active. The most used interval of use of MDT was 12 months and 80% of the cases were of the clinical multibacillary form. Anemia was detected in 42.22% of patients and approximately half of patients had complaints during treatment, mainly joint pain, headache and weakness. Therapeutic adherence was verified in 44% of the patients and 71.4% of these had more ADRs. Variant A- (A202G) was the most frequent, being observed in 19.2% of cases. Variant A (A376G) was found in 14.3% of the population studied. Thus, interventions that can improve therapeutic adherence and reduce patients' complaints about the treatment must be carried out.
Keywords: Hanseníase; Reconciliação de medicamentos; Medicamentos - Administração; Adesão à medicação; Quimioterapia combinada; Deficiência de glucosefosfato desidrogenase; CIENCIAS BIOLOGICAS: FARMACOLOGIA; Hanseníase; Poliquimioterapia; Reações adversas ao medicamento; Adesão medicamentosa; Polimorfismo; G6PD